Mewawancarai Kandidat: Strategi untuk Meningkatkan Efisiensi dan Efektivitas - Amitha Shofiani Devi; Khusnul Hotimah; Ramadhan Sakha A; Achmad Karimullah; M. Isa Anshori (Master Manajemen, 2024)
This article can provide readers with insight into the definition of interviews, types of interviews, objectives of interviews, how to behave in interviews, advantages and disadvantages of interviews as well as strategies to increase the efficiency and effectiveness of interviews. The method used in this research is a literature study by taking several journals based on fields as well as foreign language articles. The analysis used in this research is a literature review analysis. The results of this research are the importance of interviews in employee selection, so that to increase the efficiency and effectiveness of interviews, careful preparation, effective interview techniques and the use of technology are needed. Thus, companies can increase their chances of finding candidates who suit their needs.